Saneryi - Liau, Ninet Yi Ting (Nanyang Technological University, 2023)
Saneryi is a slide-and-tap puzzle game where players navigate a character around nine tiles to collect ingredients and achieve objectives. It is a mobile game created for people waiting for their cup noodles to cook, which typically takes three minutes. The aim of this project is to create a game with high replay value while playing into my strengths of creating two-dimensional assets. This project was designed as a short game planned with realistic project expectations to be achievable within the given timeframe.